Association between Helicobacter pylori seropositivity and the hemoglobin A1c/high-density lipoprotein cholesterol ratio in U.S. adults: evidence from NHANES - Xu, Cheng; Jiang, Xin-yi; Liao, Jia-ming; Zhao, Yi-fan; Hu, Jing-yi; Li, Chong-Chao; Shen, Hong (Frontiers in Nutrition, 2025)
BackgroundHelicobacter pylori (H. pylori) infection is associated with insulin resistance and metabolic syndrome. This study investigates the association between H. pylori seropositivity and the newly proposed hemoglobin A1c/high-density lipoprotein cholesterol ratio (HbA1c/HDL-C ratio) in a nationally representative U.S. population.MethodsData from the 1999–2000 National Health and Nutrition Examination Survey (NHANES) were analyzed. Multivariable linear regression models assessed the association between H. pylori seropositivity and the HbA1c/HDL-C ratio. Subgroup analyses were performed to evaluate the consistency of the association across different demographic and clinical strata. Generalized additive models with smoothing splines and threshold effect analysis was conducted to identify potential nonlinear relationships.ResultsThe cross-sectional analysis comprised 2,909 participants, including 1,254 with H. pylori seropositivity. After multivariable adjustment, a significant positive association was found between H. pylori seropositivity and the HbA1c/HDL-C ratio (β: 0.28, 95% CI: 0.13, 0.42). Subgroup analyses revealed a stronger association among non-diabetic individuals compared to diabetic individuals. A “L”-shaped relationship was observed, with an inflection point at an HbA1c/HDL-C ratio of 4.81. Below this threshold, H. pylori seropositivity was positively associated with the HbA1c/HDL-C ratio. Above this threshold, the association was no longer statistically significant.ConclusionThis study identifies a significant association between H. pylori seropositivity and the HbA1c/HDL-C ratio, suggesting that metabolic dysfunction may be linked to H. pylori infection. Future longitudinal studies are needed to establish causality and explore underlying mechanisms.